UNSUR VISUAL ARCA PARWATI SEBAGAI DASAR IDE DESAIN PERHIASAN KONTEMPORER: USING VISUAL ASPECTS OF PARWATI STATUES AS A BASIS FOR CONTEMPORARY JEWEL DESIGNIDEAS - Raissa Salsabila; Achmad Haldani Destiarmand (Universitas Trisakti, 2024)
Dynamic developments in jewelry design encourage collaboration between designers and craftsmen to continue to develop innovation and uniqueness as a characteristic and strength of an industry. This research aims to design contemporary jewelry that integrates visual elements from the Parwati statue. The research method uses qualitative and quantitative approaches. With a qualitative and quantitative approach, data was collected through literature, observation, expert interviews, and questionnaires. The research results show that integrating traditional elements with new aesthetics through resin technology and 3D printing creates artistic jewelry products relevant to Generation Z. Design exploration successfully adopts past ideas, proving that design transformation can create explorative products and attract market interest. With high market interest in Arca Parwati-inspired jewelry, this research contributes to art and design, opens up new economic opportunities, and preserves cultural heritage through unique contemporary jewelry.